Drought‐associated phenological changes of coastal marshes in Louisiana. Issue 5 (16th May 2017) - Mo, Yu; Kearney, Michael; Momen, Bahram
Abstract: Drought poses serious threats to the valuable coastal marsh ecosystems, especially considering that the frequency, intensity, and acuteness of drought may increase with prospective climate change. We study the drought‐associated phenological changes of Louisiana coastal marshes through combining remote sensing‐derived phenological record (i.e., Landsat‐derived Normalized Difference Vegetation Index, or NDVI) and field‐based environmental data during the past 30 yr. We find that drought condition in southeast Louisiana is characterized by decreased discharge of the Mississippi River and reduced precipitation, which correlate with the continental weather patterns over the conterminous United States influenced by La Niña. The peak NDVI day of saline marshes delays for two months ( P  < 0.01), from mid‐July to mid‐September, and their growth duration consequently shortens for two months ( P  < 0.01) in drought years. Such phenological changes might result from the inhibition of the growth of Spartina alterniflora, a dominant species in saline marshes whose biomass peaks earlier than the coexisting species, perhaps due to reduced freshwater input and increased water deficit. Drought might also cause Spartina dieback via similar mechanisms. Our results underline the correlation between drought in southeast Louisiana and La Niña and highlight the sensitivity of saline marshes to drought, thereby providing valuable information for coastal marsh management and conservation facing climate change.